Synthesis and in vitro Anti-Bacterial Activity of 2-(5-Nitro-2-heteroaryl)-1,3,4-Thiadiazole Derivatives - M. Yazdanian; B Zihayat; MH Moshafi; A Khodadadi; A Peimani; A Shamsaddini; M Nourhashemi; Alireza Foroumadi (Journal of Sciences, Islamic Republic of Iran)
A new series of 2-(5-nitro-2-heteroaryl)-1,3,4-thiadiazole derivatives, including nitro furan, nitro thiophene and nitro imidazole, were synthesized and screened in vitro for their inhibitory activity against eight bacterial strains. The results showed that most of the synthesized compounds were active against Gram-positive bacteria, determined by MIC method. Among them, compounds 6a, 6b and 6d exhibited strong anti-bacterial effects against the Gram-positive bacteria. The oxidation of synthesized compounds to sulfinyl and sulfonyl bearing analogues did not improve the activity.